Yoldiella A. E. Verrill & K. J. Bush 1897 - Gao, Qi; Tang, Yan; Zhang, Junlong (Zenodo, 2024)
Genus Yoldiella A. E. Verrill & K. J. Bush, 1897 Type species. Yoldiella lucida (Lovén, 1846) (International Commission on Zoological Nomenclature 1985: Opinion 1306) by original designation (Recent, North Atlantic). Published as part of Gao, Qi, Tang, Yan & Zhang, Junlong, 2024, A new species of the genus Yoldiella (Bivalvia, Protobranchia, Yoldiidae) from Haima Cold Seep, South China Sea, China, pp. 223-240 in ZooKeys 1204 on pages 223-240, DOI:10.3897/zookeys.1204.121088